Medical versus surgical methods of early abortion: protocol for a systematic review and environmental scan of patient decision aids - Rachel Thompson; Kyla Z Donnelly (BMJ Open)
Introduction Currently, we lack understanding of the content, quality and impact of patient decision aids to support decision-making between medical and surgical methods of early abortion. We plan to undertake a systematic review of peer-reviewed literature to identify, appraise and describe the impact of early abortion method decision aids evaluated quantitatively (Part I), and an environmental scan to identify and appraise other early abortion method decision aids developed in the US (Part II).Methods and analysis For the systematic review, we will search PubMed, Cochrane Library, CINAHL, EMBASE and PsycINFO databases for articles describing experimental and observational studies evaluating the impact of an early abortion method decision aid on women's decision-making processes and outcomes. For the environmental scan, we will identify decision aids by supplementing the systematic review search with Internet-based searches and key informant consultation. The primary reviewer will assess all studies and decision aids for eligibility, and a second reviewer will also assess a subset of these. Both reviewers will independently assess risk of bias in the studies and abstract data using a piloted form. Finally, both reviewers will assess decision aid quality using the International Patient Decision Aid Standards criteria, ease of readability using Flesch/Flesch-Kincaid tests, and informational content using directed content analysis.Ethics and dissemination As this study does not involve human subjects, ethical approval will not be sought. We aim to disseminate the findings in a scientific journal, via academic and/or professional conferences and among the broader community to contribute knowledge about current early abortion method decision-making support.Trial registration number This protocol is registered in the International Prospective Register of Systematic Reviews (CRD42015016717).